2023
DOI: 10.3991/ijep.v13i6.39733
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Economics Students Towards Teamwork at University

Zuzana Chmelárová,
Ladislav Pasiar

Abstract: Teamwork has an undeniable benefit in finding creative and effective solutions to situations in both work and school environments. Teamwork training can be seen as a necessary condition for the career growth of every individual. This article aims to explore students‘ attitudes towards teamwork, identify the reasons for positive and negative attitudes of students towards teamwork, and measure their level of satisfaction with various aspects of teamwork. The survey utilized a non-standardized questionnaire compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…Moreover, the study found that the top three significant soft skills for academic performance were communication, teamwork, collaboration, and time management skills. This result is consistent with previous research that found that "communication" was a core skill in higher education and the most important skill according to students [30] [31]. With effective communication and teamwork skills, students can connect with other people more easily and present their ideas and knowledge more effectively [25].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the study found that the top three significant soft skills for academic performance were communication, teamwork, collaboration, and time management skills. This result is consistent with previous research that found that "communication" was a core skill in higher education and the most important skill according to students [30] [31]. With effective communication and teamwork skills, students can connect with other people more easily and present their ideas and knowledge more effectively [25].…”
Section: Discussionsupporting
confidence: 92%